Validação de um teste rápido para tempo de protrombina em pacientes pré-cirúrgicos - Pinheiro, Janaína de Oliveira Ribeiro Avancini (Universidade do Vale do Rio dos Sinos, 2023)
One of the commonly used coagulation laboratory tests is the analysis of the prothrombin time, but its performance in its classic form involves a long response time between requesting the test, collecting the biological material, transporting it to a specialized center, processing and release of the result. Therefore, the use of a point-of-care test for coagulation allows gains in this process. The aim of this study was to validate a rapid test for prothrombin time in pre-surgical patients. The study initially went through the ethics and research committee and after approval, it was developed in two stages, between the months of August and November 2022. The first stage took place in Porto Alegre, in the region of Vale dos Sinos and in the state of Goiás, with 9 medical professionals, through an interview via Google Meet or Teams and the second stage took place by collecting blood samples from 130 adult patients, for diagnostic accuracy. The interviews were transcribed and analyzed qualitatively, with the support of the IRaMuTeQ software, which underwent a qualitative analysis and the diagnostic accuracy underwent statistical analysis with a quantitative approach. It was found that many professionals were not aware of this type of test, but consider that it would help in different situations, facilitating the provision of care. The initial prospect of this test has not yet been reached with the development of the product at this stage, since it was not possible to obtain the classification of patients with normal or altered anticoagulated status considering the INR cutoff point of 1.5.
Keywords: Coagulação sanguínea; Tempo de protrombina; Point of care; Qualidade das tecnologias da saúde; Blood clotting; Prothrombin time; Point of care; Quality of health technologies; ACCNPQ::Ciências da Saúde::Enfermagem